Synthesis of Bempedoic Acid through Electrochemical Decarboxylation of Dialkylated Malonic Acid - Xu, Zhimin; Zheng, Yue; Tian, Lifang; Wang, Yahui (Synthesis, 2021)
Bempedoic acid is a small-molecule inhibitor of adenosine triphosphate-citrate lyase (ACL) that is effective in the treatment of hypercholesterolemia and hypertension. In this paper, a new, six-step synthesis of bempedoic acid with 42% overall yield is reported. Ketone formation by electrochemical decarboxylation of dialkylated malonic acid is introduced as the key step of this process. This method uses mild conditions and its high efficiency makes it potentially suitable for industrial production.
Keywords: bempedoic acid; electrochemical synthesis; decarboxylation; malonic acid; high efficiency